Multifunctionality of the oasis ecosystem. Case study: Biskra Oasis, Algeria - FATMA ZOHRA HADAGHA; BOURHANE EDDINE FARHI; ABDALLAH FARHI; ALEXANDRU IONUT PETRISOR (Journal of Contemporary Urban Affairs, 2018)
The oasis, this green and ecological entity of the desert, a promise of life and hope in a rather unfriendly environment, has been for a long time a beneficial basis for the ecosystem services provided to human beings, for its socio-economic and urban values, and also for its ecological value. Today many ideas and concepts are developed in the scientific literature to demonstrate the benefits derived from ecosystems, such as ecosystem services, multifunctionality, and ecosystem values. However, the analyses of multifunctionality or ecosystem services of the oasis lack from the scientific literature. This study uses a literature review and a prior assessment of the oasis ecosystem services in order to create a particular conceptual framework for the oasis in an attempt to create a toolbox of variables or indicators for the evaluation of ecosystem services in the particular case of a desert ecosystem, i.e., the oasis.